Changes in the source of sedimentary organic matter in the marginal sea sediments of Eastern Hainan Island in response to human activities during the past 200 years. (8th June 2017) - Wu, Libin; Fu, Pingqing; Xu, Liqiang; Wei, Yangyang; Zhou, Xin; Li, Yeling; Wang, Xueying; Zhou, Yongli; Liu, Xiaodong
Abstract: Marine sediments have been frequently used to reconstruct the records of environment change and human activities. We collected four sediment cores from Wanquan River estuary and the eastern continental shelf of Hainan Island in the South China Sea, and analyzed the down-core physical and chemical properties of sub-samples. Based on 210 Pb dating, the longest core had a record of the most recent 200 years, while the other three profiles were slightly younger. The results show that both the TOC/TN ratios and fossil fuel-corrected organic δ 13 C of marine sediments for all four cores remained relatively constant before 1950 AD, indicating relatively stable sedimentary material sources. However, after 1950 AD, the TOC/TN ratios and organic δ 13 C in all four sediment cores displayed decreasing and increasing trends, respectively, indicating that the proportion of marine-derived material increased, whereas the land-derived materials that were mainly transported by the Wanquan River decreased. This is consistent with the obvious decrease in runoff and sediment discharges of the Wanquan River due to the increase in human activities, including industrial and agricultural production, and domestic water use in Hainan Island since 1950 AD. Therefore, we suggest that environmental changes on the land were recorded by changes in the source material of marine sediments collected from coasts and estuaries.